Clinical Improvement and P63-Deficiency Correction in OLP Patients After Photobiomodulation - Maria Zaharieva Mutafchieva; Milena Nenkova Draganova; Blagovesta Konstantinova Yaneva; Plamen Ivanov Zagorchev; Georgi Tomchev Tomov (MDPI AG, 2024)
Background: Oral lichen planus (OLP) is a chronic inflammatory disease associated with the formation of symptomatic lesions in the mouth. P63 is essential for epidermal development and regeneration. Weak expression of this protein has been shown in OLP lesions. Photobiomodulation (PBM) therapy has been reported to reduce OLP symptoms, but its ability to correct the molecular perturbations of the disease has not been studied. This study aimed to evaluate the efficacy of PBM in OLP treatment by evaluating changes in p63 expression and their association with clinical response. Methods: Twenty OLP patients underwent PBM with a diode laser (810 nm), (0.50 W, 30 s, 1.2 J/cm2), 3 times weekly for a month. The treatment efficacy index (EI) was calculated based on pain-level values and clinical scores of lesions before and after therapy. Biopsies were taken before and after therapy, analyzed immunohistochemically for p63 expression, and compared with 10 healthy controls. Results: P63 levels in OLP lesions were significantly lower than those in normal oral mucosa. After treatment, the pain level and clinical scores of the lesions decreased significantly. The calculated EI showed PBM effectiveness in 90% of cases. Increased p63 positivity and staining intensity were observed after therapy. Conclusions: The established p63 deficiency in OLP lesions is likely an important molecular mechanism in the pathogenesis of the disease. Laser irradiation at 810 nm increased p63 expression to a level close to that found in the healthy epithelium and significantly improved the symptoms and clinical signs of OLP. All of this determines the effectiveness of PBM therapy in the management of OLP.